Assessing Parallel Texts in Legal Translation - Leung, Matthew (The Journal of Specialised Translation, 2004)
Sarcevic in New Approach to Legal Translation (1997: 71) writes, in connection with parallel legal texts, "While lawyers cannot expect translators to produce parallel texts which are equal in meaning, they do expect them to produce parallel texts which are equal in legal effect. Thus the translator's main task is to produce a text that will lead to the same legal effects in practice". This paper explores the implications of such an approach to the assessment of the 'success' of a piece of legal translation and bilingual legal drafting to (a) general translation theory, and (b) legal translation assessment practice in the academic context. The preceding quotation would suggest that a judge is in the position of the ultimate judge of the quality of the parallel legal texts. Moreover, he/she has at his/her disposal, a panoply of interpretation rules to help him/her reconcile discrepancies in parallel texts. However, is such an authority just a beautiful fiction? And can general interpretation rules be established that apply to non-legal texts? Whatever the answers, the judge's attempt to reconcile discrepancies already provides an interesting lesson to the translation teacher-assessor in the approach to translation assessment.